Pengklasifikasian Tingkat Kesejahteraan Keluarga Di Desa Citamiang Dengan Penerapan Logika Fuzzy Model Tahani - Yoga Permana; Lelah Lelah (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2020)
Indonesia is a country with a substantial population population, in the year 2020 the population of Indonesia reaches 269.6 million. Each of them certainly has a family. Family welfare not only affects the success of its family, but also affects the success of the government, no exception of village governance. Therefore, information about the family welfare level is necessary to review the efforts that the Government has made if it is successful or not. To determine the level of family welfare there are several indicators such as income, occupation, age and dependents. In order to classify the family welfare process can be more efficient, it can be processed through programs that apply Fuzzy logic with Tahani model. The purpose of the study was intended to classify the welfare of the family based on population data owned by the village government. Based on the research results obtained by Fuzzy logic with Tahani model can be used to process population data in accordance with the level of family welfare indicators by providing output in the form of classifications of families including incapacitated families, underprivileged families and privileged families. The output of the program was also tested with the fuzzyTECH application to measure the success of Fuzzy logic on the built program.